ART-PEDAGOGIKANING OʻQUVChILAR ESTETIK TARBIYASI VA IJODIY FIKRLAShIGA TA’SIRI - Paxratdinova, U.K. (SCIENCE and SOCIETY, 2025)
This article explores the application of art-pedagogical approaches in general school education as a means of fostering aesthetic development. It highlights the potential of art to enhance students’ creativity, stimulate their interest in artistic activities, and broaden their aesthetic worldview. Based on practical observations, the effectiveness of integrating artistic tools into lessons is analyzed, and the relevance of introducing art-pedagogical methods into the general education system is substantiated.